Chondroprotective Potential of Oleocanthal and Hydroxytyrosol from Extra Virgin Olive Oil: A Meta-Analysis - Muhammad Addien Prima Nanda; Muhammad Reagen (HM Publisher, 2025)
Background: Osteoarthritis (OA) is a prevalent degenerative joint disease characterized by cartilage degradation, inflammation, and pain. Oleocanthal and hydroxytyrosol, two potent anti-inflammatory and antioxidant polyphenols found in extra virgin olive oil (EVOO), have shown promising chondroprotective effects in preclinical studies. This meta-analysis aimed to evaluate the efficacy of oleocanthal and hydroxytyrosol in preventing cartilage degradation and ameliorating OA symptoms. Methods: A systematic search of electronic databases (PubMed, Scopus, and Web of Science) was conducted to identify relevant studies published between 2013 and 2024. Randomized controlled trials (RCTs) and preclinical studies investigating the effects of oleocanthal or hydroxytyrosol on OA were included. The primary outcome was cartilage degradation, assessed by imaging or histological scores. Secondary outcomes included pain and inflammation. Results: Nine studies (4 RCTs and 5 preclinical studies) met the inclusion criteria. The RCTs included a total of 315 participants with knee OA. The interventions consisted of oral administration of oleocanthal or hydroxytyrosol at various doses and durations. The preclinical studies used different in vivo animal models. Pooled analysis of the RCTs showed that oleocanthal or hydroxytyrosol significantly reduced cartilage degradation compared to control (SMD = -0.85, 95%CI -1.20 to -0.50, p < 0.001). In the preclinical studies, oleocanthal and hydroxytyrosol also significantly reduced cartilage degradation scores (SMD = -1.10, 95%CI -1.50 to -0.70, p < 0.001). Pooled analysis of pain outcomes showed a significant reduction with oleocanthal or hydroxytyrosol compared to control (Preclinical: SMD = -0.60, 95%CI -0.90 to -0.30, p < 0.001; RCTs: SMD=-1.20, 95%CI-1.60 to -0.80, p < 0.001). Oleocanthal and hydroxytyrosol significantly reduced inflammatory markers (Preclinical: SMD = -0.85, 95%CI-1.15 to -0.55, p < 0.001; RCTs: SMD= -1.50, 95%CI-1.90 to -1.10, p < 0.001). Conclusion: This meta-analysis provides evidence for the chondroprotective potential of oleocanthal and hydroxytyrosol from EVOO. These polyphenols may offer a promising therapeutic strategy for preventing cartilage degradation, reducing pain, and improving OA symptoms. Further large-scale RCTs are warranted to confirm these findings and establish optimal dosage and treatment duration.